Keeping life of cut carnation - Jung, Maeli; Normann Kâmpf, Ate Lene (Pesquisa Agropecuaria Brasileira, 2014)
Keeping life of cut carnation 'White Sim', 'Le Réve' and 'Scania' were tested through five treatments: 1. distilled water (control); 2. a solution of Al-K-sulphate, KCl, NaCl and sugar; 3, a solution of Cu-sulphate, KCl and NaCl and sugar; 4. a solution of silver-nitrate and sugar; 5. a solution of silverthio-sulphate and sugar. The evaluated characters were fresh weight after three days, flower quality after five days, and keeping life in total days. The results indicated the solution silverthio-sulphate as the best treatment. Significant differences were found between the cultivars: 'Le Rêve' and 'White Sim' show to be more resistent than 'Scania'.